EFEKTIVITAS BANTUAN PENINGKATAN INDEKS PERTANAMAN MELALUI KLASTER TERHADAP PENINGKATAN PENDAPATAN USAHATANI PADI DI KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS - Saragih, Origen J.F.; Erlina, Yuni; Anggreini, Trisna (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2020)
This study aims to determine the description of cluster rice farming in Warna Sari Village; analyzing the effectiveness of assistance to increase the cropping index through clusters to increase rice farming income in Warna Sari Village, Tamban Catur, Kapuas Regency. The research was conducted in the Warna Sari village subdistrict Tamban Catur Kapuas District, sampling methods intentionally that farmers who are members and actively participate in the program. To answer the research objectives, direct interviews were conducted with farmers who were equipped with a questionnaire that had been provided. The analysis used is the analysis of farm income; descriptive statistical analysis; paired sample t-test. The results of this study indicate that after the cluster program farmers can carry out two planting seasons in one year. The types of seeds used were Karang Dukuh local siam rice and Inpara 3 superior rice. The use of production facilities after the cluster was more efficient than before the cluster. The average income before the cluster was IDR. 16,060,893 and after the cluster was IDR. 35,833,943 with a difference of IDR. 19,773,050. Sig value. obtained is 0.02 <0.05, which states that the cluster is effective in increasing rice farming income in Warna Sari Village.